(untitled) (River Edge, NJ, 2003)
This book focuses on current topics in astronomy, astrophysics and nuclear astrophysics. The areas covered are: origin of the universe and nucleosynthesis; chemical and dynamical evolution of galaxies; nova/supernova and evolution of stars; astrophysical nuclear reaction; structure of nuclei with unstable nuclear beams; origin of the heavy element and age of the universe; neutron star and high density matter; observation of elements; high energy cosmic rays; neutrino astrophysics.
Keywords: Nucleosynthesis,Galaxies,Tổng hợp hạt nhân,Thiên hà; Evolution,Phát triển